Herbal ingredients in anti-aging cream formulations: A comprehensive review of their bioactive components, molecular mechanisms, and dermatological benefits - Yıldırım, Aybeniz; Yücer, Rümeysa; Şen, Ali; Bitiş, Leyla (Elsevier B.V., 2025)
The growing interest in anti-aging skincare products has led to increased scrutiny of synthetic ingredients, resulting in a shift toward plant-based alternatives. This review provides a comprehensive analysis of the bioactive compounds present in herbal ingredients commonly used in anti-aging cream formulations and their dermatological benefits. For this purpose, anti-aging creams listed under the cosmetics section of RxMediaPharma® 2025 were examined, and their botanical components were identified. A detailed literature search was conducted using PubMed, Scopus, Google Scholar, Embase, and Web of Science to determine the bioactive constituents and their effects. The study identified a total of 215 plant species frequently used in anti-aging formulations. Among them, Aloe vera, Simmondsia chinensis (jojoba), and Vitis vinifera (grape seed) were the most commonly utilized. The presence of flavonoids, polyphenols, tannins, vitamins (A, C, E), and essential minerals such as selenium and zinc was highlighted as key contributors to their anti-aging properties. These bioactive compounds exhibit antioxidant, anti-inflammatory, moisturizing, and collagen-boosting effects, making them valuable ingredients in cosmetic formulations. In conclusion, the widespread use of plant-based ingredients in anti-aging skincare underscores their dermatological potential. However, further preclinical and clinical studies are needed to validate their efficacy and safety, ensuring their standardized use in cosmetic applications. © 2025 Elsevier Ltd
Keywords: Anti-aging; Antioxidants; Bioactive compounds; Dermatology; Herbal cosmetics; Plant-based skincare